Decomposition rate of extraradical hyphae of arbuscular mycorrhizal fungi decreases rapidly over time and varies by hyphal diameter and season. (September 2019) - Schäfer, Holger; Dannoura, Masako; Ataka, Mioko; Osawa, Akira
Abstract: Understanding how extraradical mycorrhizal fungal hyphae (EMH) regulate the cycling and retention of plant-assimilated carbon (C) in forest soils requires estimation of the production, mortality, and decomposition of EMH. To do this, the use of mass-balance models in combination with hyphal in-growth mesh bags ("in-growth bags") was proposed in recent studies. However, poor knowledge on the decomposition of field-grown EMH prevents confirmation of assumed EMH decomposition dynamics. In this study, we determined the decrease in hyphal length density of field-grown EMH of arbuscular mycorrhizal fungi (AM) over eight months in in-growth bags incubated in a warm-temperate Chamaecyparis obtusa forest, to study EMH decomposition under field conditions. We used exponential decay models to describe the changes in the decomposition rate of EMH over the incubation time, between EMH diameter classes, and between seasons. A rapid decrease of the decomposition rate of EMH within two months from 2.5 to 0.1 month −1 was estimated, corresponding to an increase in half-life from 0.3 to 7 months. Furthermore, significant differences in the initial maximum decomposition rate were estimated between fine (1.6 month −1 ; minimum half-life: 0.4 months) and coarse EMH (3.1 month −1 ; minimum half-life: 0.2 months) and between incubations during spring-summer (April and August; 2.7 month −1 ; minimum half-life: 0.3 months) and autumn-winter (October and February; 1.1 month −1 ; minimum half-life: 0.6 months). This large variability in the decomposition rates of EMH of AM fungi has to be considered in mass-balance models to estimate C fluxes between plants, soil, and the atmosphere. Highlights: 40–78% of mycorrhizal fungal hyphal litter disappears within one month. Fungal hyphal decomposition has slowed rapidly by the second month. Decomposition rate of fungal hyphae follows an exponential decay to a minimum. Decomposition of fungal hyphae varies between seasons and diameter classes.